Late Wisconsinan and Holocene History of the Laurentide Ice Sheet - Dyke, Arthur; Prest, Victor (Géographie physique et Quaternaire, 1987)
AbstractEleven paleogeographic maps and a summary ice retreat map outline the history of advance, retreat, and readvances of the Laurentide Ice Sheet along with associated changes in proglacial drainage and relative sea level oscillations for Late Wisconsinan and Holocene times. The text outlines pertinent chronological control and discusses the paleoglaciology of the ice sheet, with attention to location and migration of ice divides, their attendant domes and saddles, and to ice streams, ice shelves, and mechanisms of déglaciation. At 18 ka the ice sheet consisted of 3 sectors with an interlocked system of ice divides joined at intersector saddles. A throughgoing superdivide is recognized and named the Trans Laurentide Ice Divide. The ice sheet retreated slowly from 18 to 13 ka, mainly along the west and south margins, but still held a near maximum configuration at 13 ka. A regional change in flow pattern over the Prairies just before 14 ka is thought to represent a large reduction in ice volume, but not in extent, and likely was triggered by a switch from nondeforming to deforming bed conditions. Retreat between 13 and 8 ka was vastly more rapid in the west than in the east, which resulted in eastward migration of the divide system of Keewatin Ice but relatively static divides of Labrador and Foxe Ice. By 10 ka the Trans Laurentide Ice Divide had been fragmented as Hudson Ice became increasingly autonomous. By 8 ka Hudson Ice had disappeared, little ice was left in Keewatin, but Foxe Ice still held its near maximum configuration and Labrador Ice was still larger than Foxe Ice. Repeated surging along aquatic margins and calving back of margins thinned by surging probably was the most important mechanism of deglaciation of Keewatin and Hudson Ice. The core of Foxe Ice disintegrated at 7 ka but retreat and readvance of Foxe Ice remnants continued throughout the Holocene.